Experimental evaluation of a prototype hybrid CPV/T system utilizing a nanoparticle fluid absorber at elevated temperatures. (15th October 2018) - Otanicar, Todd; Dale, John; Orosz, Matthew; Brekke, Nick; DeJarnette, Drew; Tunkara, Ebrima; Roberts, Kenneth; Harikumar, Parameswar
Graphical abstract: Highlights: Experimental demonstration of hybrid CPV/T collector operating over 100 C using nanoparticle filter with flowing fluid. Nanoparticle filter utilizes UV/Visible absorption with gold particles and infrared absorption with ITO. Thermal and electrical efficiency of 61% and 4% respectively at 110 C. Abstract: Novel approaches for solar energy conversion continue to garner interest as a potential thermal and electrical energy source. Additionally, the need for systems capable of producing thermal energy at temperatures up to 300 °C is growing as a means to provide process heat to industry and distributed generation for small communities. An approach that has seen recent increased interest is the hybrid concentrating photovoltaic/thermal collector that can co-produce electricity and heat energy above 100 °C. One technique for this is to use nanoparticles in the heat transfer fluid to spectrally filter off wavelengths poorly utilized by the photovoltaic component. Here, we have demonstrated the first on-sun operation of a nanoparticle based hybrid CPV/T solar collector at temperatures exceeding 100 °C using a combination of gold and indium tin oxide nanoparticles in Duratherm S flowing in the receiver, with an aperture area a full order of magnitude larger than other tests. At 14× concentration the system achieved a photovoltaic efficiency of 4% while achieving a peak thermal efficiency of 61% with an outlet temperature of the fluid of 110 °C.